Obacunone reduces inflammatory signalling and tumour occurrence in mice with chronic inflammation-induced colorectal cancer. (1st January 2020) - Luo, Xiaoping; Yu, Zhilun; Yue, Bei; Ren, Junyu; Zhang, Jing; Mani, Sridhar; Wang, Zhengtao; Dou, Wei
Abstract: Context: Obacunone, a limonoid abundantly found in Citrus fruits, exhibits a variety of bioactivities. Objective: To investigate the effects of obacunone on a colorectal cancer (CRC) mouse model, and clarify its potential molecular mechanisms. Materials and methods: The male Balb/c mice were induced with azoxymethane and dextran sulfate sodium for 12 weeks. Obacunone (50 mg/kg) was administered via oral gavage three times every week until the end of the experiment. Disease indexes including body weight, spleen weight, bloody diarrhea, colon length, histopathological score, and tumor size were measured. The anti-proliferation activities of obacunone were analyzed by MTT or flow cytometry. The expression of protein and mRNA related to cell proliferation or inflammatory cytokines was determined by Western blot, q-PCR and IHC. Results: Obacunone significantly alleviated bloody diarrhea, colon shortening (7.35 ± 0.2128 vs. 8.275 ± 0.2169 cm), splenomegaly, histological score (9 ± 0.5774 vs. 6 ± 0.5774) and reduced tumor size (4.25 ± 0.6196 vs. 2 ± 0.5669). Meanwhile, the expression of protein and mRNA related to cell proliferation or inflammatory cytokines was remarkably decreased in tumor tissue. Obacunone inhibited the proliferation activities of colorectal cancer cells. Moreover, obacunone induced colorectal cancer cells G1 and G2 phases arrest, and suppressed the expression of cell cycle genes. Conclusions: Obacunone could alleviate CRC via inhibiting inflammatory response and tumor cells proliferation. The results may contribute to the effective utilization of obacunone or its derivatives in the treatment of human CRC.